Karakterisasi Konstanta Dielektrik dan Kapasitansi pada Lemak Hewani dengan Menggunakan Variasi Suhu dan Frekuensi - Noer Rimafatin; Bowo Eko Cahyono; Misto Misto (Lambung Mangkurat University Press, 2019)
Fat is a food substance that is very important to maintain the health of the human body. One source of fat is animal fat. Differences in the type of fat can be known based on the electrical properties of materials such as dielectric constant and capacitance. The purpose of this research is to know the characteristic of dielectric constant and capacitance in animal fat by giving treatment of temperature and frequency variation. This research uses parallel plate capacitor method which is connected to the source of alternating current input voltage and voltmeter as the output voltage meter. The samples studied were chicken fat and beef fat. This research uses input voltage with frequency of 1kHz up to 20kHz, while temperature that is used is varied from 45⁰C decrease to 30⁰C. The results obtained from this study show that the increasing frequency results to the decreasing values of capacitance and dielectric constant in chicken fat and cow fat. The effect of temperature on the capacitance and dielectric constant of chicken fat and cow fat shows non linear relationship